Riverine Ecosystem Management Science for Governing Towards a Sustainable Future (Aquatic Ecology Series ;, 2018)
This open access book surveys the frontier of scientific river research and provides examples to guide management towards a sustainable future of riverine ecosystems. Principal structures and functions of the biogeosphere of rivers are explained; key threats are identified, and effective solutions for restoration and mitigation are provided. Rivers are among the most threatened ecosystems of the world. They increasingly suffer from pollution, water abstraction, river channelisation and damming. Fundamental knowledge of ecosystem structure and function is necessary to understand how human acitivities interfere with natural processes and which interventions are feasible to rectify this. Modern water legislation strives for sustainable water resource management and protection of important habitats and species. However, decision makers would benefit from more profound understanding of ecosystem degradation processes and of innovative methodologies and tools for efficient mitigation and restoration. The book provides best-practice examples of sustainable river management from on-site studies, European-wide analyses and case studies from other parts of the world. This book will be of interest to researchers in the field of aquatic ecology, river system functioning, conservation and restoration, to postgraduate students, to institutions involved in water management, and to water related industries.